STUDI ADSORBSI LOGAM BESI (Fe) DAN MANGAN (Mn) PADA AIR ASAM TAMBANG OLEH KOMPOSIT: CLAYSTONE – ZEOLIT - KARBON AKTIF TERAKTIVASI ADSORPTION STUDY OF LOGAM BESI (Fe) AND MANGANESE (Mn) ON ACID MINE WATER BY CLAYSTONE COMPOSITE - ZEOLITE - ACTIVATED CARBO - Ginting, Emdananta; Devy, Shalaho Dina; Henny Magdalena; Oktaviani, Revia; Respati, Lucia Litha (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
Composites are a combination of two or more different materials and their properties to form new materials that have better characteristics. The composite was previously composed of activated claystone, activated zeolite, and coconut shell activated charcoal with 3 ratios, namely: (claystone [C] : zeolite [Z] : activated charcoal [A] = 60:20:20; 20:20:60; and 20:60:20. This composite acts as an adsorbent in the adsorption process of acid mine water samples. Based on the results of the adsorption test, it was concluded that the composite cannot neutralize the pH of acid mine water. Of the three types of composites, Composite A (claystone [C] : zeolite [Z] : activated charcoal [A] = 60:20:20) showed a significant influence with a decrease in the concentration of heavy metals Iron and Manganese within 30 min of contact time. Fe adsorption capacity is 20,7 mg/g and Mn is 24,3 mg/g.